Value in the accumulated experience - Callaghan, Andrew (2016)
Over the last decade access to cheap enabling technology has promoted widespread practitioner interest in online service propositions. In support of these propositions technology has become prominently established within the firm-consumer interface through self-service technologies (SSTs). SSTs are attractive to firms due to opportunities for cost reduction and the targeting of previously in-accessible customer segments. This attractiveness has led to an increasing shift in the mode of service provision from traditional personal service delivery to SSTs, which have evolved from limited time saving alternatives to the proliferation of chargeable subscription-based services in operation today. However, the viability of these channels relies on the customers’ perception of value creation and the degree to which the SST contributes to it. Consequently, realising the potential benefits from SSTs has continued to be problematic for firms as they still have a poor understanding of how value is co-created across technology interfaces. Key to understanding this phenomenon is how value emerges through the customer experience, which has now transcended the traditional consumer/firm perspective to include the users’ wider social network of actors. This is a gap in the literature and an important area of enquiry since it directly affects subscription channel uptake and long-term customer retention.